Community educational work, youth participation and social innovation. A research in three alpine valleys - Valenzano, Nicolò (Formazione & insegnamento, 2021)
Community educational work in the Alpine areas can facilitate the participation and community commitment of young people and stimulate social innovation: to do this, it is important to transform Alpine communities into capabilities contexts. Starting from this framework, the paper presents an action-research in progress in three Alpine valleys, in the north-west of Italy, on the relationship of young people with their territory and job opportunities. Starting from the data that emerged, in the third section I propose some indications for the socio-educational intervention. Finally, I show the possible link between community educational work, social innovation and local development in mountain areas.